The Aryl Hydrocarbon Receptor (AhR) Is a Novel Gene Involved in Proper Physiological Functions of Pancreatic β-Cells - Shuhd Bin Eshaq; Jalal Taneera; Shabana Anjum; Abdul Khader Mohammed; Mohammad H. Semreen; Karem H. Alzoubi; Mohamed Eladl; Yasser Bustanji; Eman Abu-Gharbieh; Waseem El-Huneidi (Cells)
The Kynurenine pathway is crucial in metabolizing dietary tryptophan into bioactive compounds known as kynurenines, which have been linked to glucose homeostasis. The aryl hydrocarbon receptor (AhR) has recently emerged as the endogenous receptor for the kynurenine metabolite, kynurenic acid (KYNA). However, the specific role of AhR in pancreatic β-cells remains largely unexplored. This study aimed to investigate the expression of AhR in human pancreatic islets using publicly available RNA-sequencing (RNA-seq) databases and to explore its correlations with various metabolic parameters and key β-cell markers. Additionally, functional experiments were conducted in INS-1 cells, a rat β-cell line, to elucidate the role of Ahr in β-cell biology. RNA-seq data analysis confirmed the expression of AHR in human islets, with elevated levels observed in pancreatic islets obtained from diabetic and obese donors compared to non-diabetic or lean donors. Furthermore, AHR expression showed an inverse correlation with the expression of key β-cell functional genes, including insulin, PDX-1, MAFA, KCNJ11, and GCK. Silencing Ahr expression using siRNA in INS-1 cells decreased insulin secretion, insulin content, and glucose uptake efficiency, while cell viability, apoptosis rate, and reactive oxygen species (ROS) production remained unaffected. Moreover, Ahr silencing led to the downregulation of major β-cell regulator genes, Ins1, Ins2, Pdx-1, and Glut2, at both the mRNA and protein levels. In summary, this study provides novel insights into the role of AhR in maintaining proper β-cell function. These findings suggest that AhR could be a potential target for future therapeutic strategies in treating type 2 diabetes (T2D).